Combined apatite, biochar, and organic fertilizer application for heavy metal co-contaminated soil remediation reduces heavy metal transport and alters soil microbial community structure - Hong, Yi; Li, Dong; Xie, Can; Zheng, Xiaoxiao; Yin, Jing; Li, Zhidong; Zhang, Kailu; Jiao, Yangqiu; Wang, Baijie; Hu, Yueming; Zhu, Zhiqiang (The Science of the total environment, 2022)
Soil amendments are used extensively to remediate soils contaminated with heavy metals. However, the effects of soil amendments on heavy metal bioavailability, plant yield, and bacterial community structure in tropical farmland soils remain largely unknown. In the present study, seaweed organic fertilizer (S), apatite (A), biochar (B), and seaweed organic fertilizer-apatite-biochar mixtures (SAB) were applied at different rates to assess their influence on cadmium (Cd), lead (Pb), and chromium (Cr) bioavailability in contaminated farmland soils, using different component ratios and doses in maize field plots, and maize yield. Effects on soil bacterial community structure were also evaluated based on high-throughput sequencing. Following addition of 2 % S + A + B combined amendment at a ratio of 1:0.5:1.5 (2%S1A0.5B1.5), soil pH and electrical conductivity (EC) were elevated, and bioavailable Cd, Pb, and Cr concentrations were reduced in potted soils, leading to higher heavy metal immobilization. Under field conditions, soil pH, EC, organic matter, ammonium‑nitrogen, available phosphorus, available potassium, and crop productivity were all increased considerably, whereas soil Cd and Cr bioavailability were lower in the combined amendment treatments than in the control treatments. Particularly, application of a 2.49 t·ha−1 combined amendment (0.83 t·ha−1 S + 0.41 t·ha−1A + 1.25 t·ha−1B,1:0.5:1.5) decreased Cd, Pb, and Cr concentrations in maize grain by 68.9 %, 68.9 %, and 65.7 %, respectively. Species abundance and evenness in bacterial communities increased in field soils subjected to combined amendments, with shifts in community structure and function mostly driven by changes in soil pH, organic matter content, and nutrient availability. Overall, the results suggest that 1.5%S1A0.5B1.5 is the optimal treatment for remediating heavy metal co-contaminated soil, and thereby, improving maize yield and quality. Combined organic and inorganic amendments achieve high remediation efficiency, mainly by improving chemical properties, reducing heavy metal bioavailability, and altering bacterial community structure and function in heavy metal contaminated farmland soils. [Display omitted] •Cd, Pb, and Cr co-contaminated soils remediated with combined amendments.•Combined amendments improved soil and altered soil bacterial community structure.•Maize plant growth enhanced in co-contaminated soils receiving combined amendments.